2018
DOI: 10.1002/jso.25192
|View full text |Cite
|
Sign up to set email alerts
|

CD90 expression in human intrahepatic cholangiocarcinoma is associated with lymph node metastasis and poor prognosis

Abstract: CD90 cells demonstrate high metastatic potential owing to Wnt/β-catenin signaling activation and are associated with poor prognosis in ICC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 29 publications
(27 reference statements)
1
19
0
Order By: Relevance
“…Treatment of CCA depends on the anatomical location, but there are some surgical concerns remain further verification, including the use of lymph node dissection, liver transplantation, adjuvant chemotherapy, and target therapies (17)(18)(19)(20). In most surgery centers, lymph node metastasis is considered a contraindication for surgical options, but it is considered resectable when it is limited to be regional in partial hospitals (21,22). In the present study, lymph node metastasis was found to be an independent prognostic factor for both OS and TS in iCCA and hiCCA, but not in dCCA.…”
Section: Discussionsupporting
confidence: 44%
“…Treatment of CCA depends on the anatomical location, but there are some surgical concerns remain further verification, including the use of lymph node dissection, liver transplantation, adjuvant chemotherapy, and target therapies (17)(18)(19)(20). In most surgery centers, lymph node metastasis is considered a contraindication for surgical options, but it is considered resectable when it is limited to be regional in partial hospitals (21,22). In the present study, lymph node metastasis was found to be an independent prognostic factor for both OS and TS in iCCA and hiCCA, but not in dCCA.…”
Section: Discussionsupporting
confidence: 44%
“…Stromal PDGFRa was found to decrease with tumor progression [33][34][35] , while a high expression of stromal PDGFRb was associated with a worse prognosis in different solid tumors [36][37][38][39][40][41][42] and drug resistance 43 . Likewise, CD90 defined fibroblasts were adversely associated with clinical outcome 44,45 but were also discussed as immune-regulatory fibroblasts [46][47][48] .…”
mentioning
confidence: 99%
“…The methylation of DLEC1 cilia and flagella associated protein is engaged in a favorable clinical outcome and prognosis in patients with small duct ICC [6]. However, CD90 expression contributed to lymph node metastasis and thereby leads to a poor prognosis in patients with ICC [7]. The expression of VEGFR-3 in ICC also promotes the angiogenesis of lymph, thereby resulting in an unfavorable prognosis [8].…”
mentioning
confidence: 99%